(untitled) (Colombia Medica, 2007)
The historical investigation as well as a critical assessment of previous events related to nursing, reveal their effects on nursing present behaviours and practice. Nursing as science and discipline is constituted by memorable facts; nursing is the science of human existence in time; it comes from the past and goes to the future; as others sciences, it has been built slowly through three stages: knowledge, ethics, and aesthetics. The symbols of the oldest art and youngest profession -nursing should be orientated with critical sense and in accordance with current practices in the discipline.